Epitaxial growth of Pd clusters on N-doped Ag nanowires for oxygen reduction reaction - Qinhe Guan; Shiwei Sun; Xiaohang Ge; Fan Zhang; Lijie Qu; Chao Yin; Weiyong Yuan; Lianying Zhang (ChemPhysMater)
Efficient and stable Pt-free electrocatalysts for oxygen reduction reaction (ORR) are indispensable for future fuel cells. Herein, we describe a heterostructure of Pd nanocrystals (PdNCs) on N-doped Ag nanowires (NWs) synthesized using a direct epitaxial growth strategy with a Pd loading of only 9.5 wt.%. The PdAg bimetallic heterostructure showed the highest mass activity among reported PdAg-based ORR electrocatalysts and exhibited excellent stability, with only a 1.5 mV decay in the half-wave potential even after 20000 cycles of continuous testing. The remarkably enhanced activity and durability can be attributed to the distinct advantages of the ultrasmall PdNCs, cocatalysts of N-doped AgNWs, and their heterointerfaces. This work reveals that the epitaxial growth of a heterostructure on a stable support is a promising strategy for promoting catalytic performance.